Effects of Mobile Text Messaging on Glycemic Control in Patients With Coronary Heart Disease and Diabetes Mellitus: A Randomized Clinical Trial. Issue 9 (September 2019) - Huo, Xiqian; Krumholz, Harlan M.; Bai, Xueke; Spatz, Erica S.; Ding, Qinglan; Horak, Paul; Zhao, Weigang; Gong, Qiuhong; Zhang, Haibo; Yan, Xiaofang; Sun, Ying; Liu, Jiamin; et al.
Abstract : Background: Mobile health interventions may support risk factor management and are readily scalable in healthcare systems. We aim to evaluate the efficacy of a text messaging–based intervention to improve glycemic control in patients with coronary heart disease and diabetes mellitus in China. Methods and Results: The CHAT-DM study (Cardiovascular Health and Texting-Diabetes Mellitus) was a parallel-group, single-blind, randomized clinical trial that included 502 patients with both coronary heart disease and diabetes mellitus from 34 hospitals in China. The intervention group (n=251) received 6 text messages per week for 6 months in addition to usual care. Messages were theory driven and culturally tailored to provide educational and motivational information on glucose monitoring, blood pressure control, medication adherence, physical activity, and lifestyle. The control group (n=251) received usual care and 2 thank you messages per month. The primary outcome was change in glycated hemoglobin (HbA1C [hemoglobin A1C ]) from baseline to 6 months. Secondary outcomes were change in proportion of patients achieving HbA1C <7%, fasting blood glucose, systolic blood pressure, LDL (low-density lipoprotein) cholesterol, body mass index, and physical activity from baseline to 6 months. The end points were assessed using analyses of covariance. The follow-up rate was 99%. When compared with control group at 6 months, the intervention group had a greater reduction in HbA1C (−0.2% versus 0.1%; P =0.003) and a greater proportion of participants who achieved HbA1C <7% (69.3% versus 52.6%; P =0.004). Change in fasting blood glucose was larger in the intervention group (between-group difference: −0.6 mmol/L; 95% CI, −1.1 to −0.2; P =0.011), but no other outcome differences were observed. Nearly all participants reported that messages were easy to understand (97.1%) and useful (94.1%). Conclusions: A text message intervention resulted in better glycemic control in patients with diabetes mellitus and coronary heart disease. While the mechanism of this benefit remains to be determined, the results suggest that a simple, culturally sensitive mobile text messaging program may provide an effective and feasible way to improve disease self-management. Clinical Trial Registration: URL: http://www.clinicaltrials.gov . Unique identifier: NCT02883842. Abstract : Supplemental Digital Content is available in the text.